2015
DOI: 10.1186/s13065-015-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

An experimental method to study emissions from heated tobacco between 100-200°C

Abstract: BackgroundCigarette smoke emissions are mainly produced by distillation, pyrolysis and combustion reactions when the tobacco is burnt. Some studies have shown that heating tobacco to temperatures below pyrolysis and combustion temperatures has the potential to reduce or eliminate some toxicants found in cigarette smoke. In this study, we designed a bench-top tube furnace that heats tobacco between 100-200°C and systematically studied the effects of heating temperatures on selected gas phase and aerosol phase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 37 publications
1
21
1
Order By: Relevance
“…The lower nicotine yield can be explained by the fact that the maximum temperature achieved by the electric heat source was lower than charcoal (see online supplementary figure S–1). Similar to what was reported for heated cigarettes,71 a direct relationship between temperature of the heated tobacco and mainstream nicotine yields is likely for waterpipe tobacco, but more data are needed. Should this relationship prove robust, product standards regarding the acceptable range of power for electric waterpipe heating devices would be warranted.…”
Section: Discussionsupporting
confidence: 62%
“…The lower nicotine yield can be explained by the fact that the maximum temperature achieved by the electric heat source was lower than charcoal (see online supplementary figure S–1). Similar to what was reported for heated cigarettes,71 a direct relationship between temperature of the heated tobacco and mainstream nicotine yields is likely for waterpipe tobacco, but more data are needed. Should this relationship prove robust, product standards regarding the acceptable range of power for electric waterpipe heating devices would be warranted.…”
Section: Discussionsupporting
confidence: 62%
“…Although the core operating temperature of THS 2.1 is slightly above the temperature range characterized by Foster et al 21 for TSNAs, the circular temperature distribution profile in the tobacco plug of THS 2.1, with temperatures decreasing rapidly from the inner core of the tobacco plug to well below 100°C on the outer surface, contributes significantly to the reduced release and direct transfer of TSNAs into the aerosol of THS 2.1 compared to CC. In addition, the amount of tobacco contained in THS is significantly less than in CC which adds to the reduced amount of TNSAs released with THS 2.1.…”
Section: Discussionmentioning
confidence: 73%
“…A recent study by Forster et al 21 demonstrated that the evaporative transfer of NNK present in cured tobacco to the mainstream aerosol occurs at low temperatures but to the most extend above 120°C to 140°C, although no clear linearity could be shown. Furthermore, the authors showed that the percentage of TSNAs released from the tobacco into the aerosol at the temperatures assessed in this study (100°C to 200°C) was very low (<10%) compared to the available amounts in the used tobacco rod.…”
Section: Discussionmentioning
confidence: 99%
“…Public Health England recently reported that e-cigarettes were likely to be 95% less harmful than tobacco products and could be a means for smokers to quit or reduce their consumption of cigarettes. (Forster et al., 2015 ; Nutt et al., 2014 ; Public Health England, 2015 ; West et al., 2015 ). The evidence was based on the composition and quantities of constituents found in e-cigarette aerosols and the relative risk associated with the main components.…”
Section: Introductionmentioning
confidence: 99%